Theranostic Nanoparticles with Controlled Release of Gemcitabine for Targeted Therapy and MRI of Pancreatic Cancer - Lee, Gee Young (2013)
The tumor stroma in human cancers significantly limits the delivery of therapeutic agents into cancer cells. To develop an effective therapeutic approach overcoming the physical barrier of the stroma, we engineered urokinase plasminogen activator receptor (uPAR)-targeted magnetic iron oxide nanoparticles (IONPs) carrying gemcitabine (Gem) as a chemotherapy drug for targeted delivery into uPAR-expressing tumor and stromal cells. The uPAR-targeted nanoparticle construct, ATF-IONP-Gem, was prepared by conjugating IONPs with the amino-terminal fragment (ATF) peptide of the receptor-binding domain of uPA, a natural ligand of uPAR, and Gem via a lysosomally cleavable tetrapeptide linker. These theranostic nanoparticles enable intracellular release of Gem following receptor-mediated endocytosis of ATF-IONP-Gem into tumor cells, and also allow in vivo magnetic resonance imaging (MRI) of tumors. Our results demonstrated the pH- and lysosomal enzyme-dependent release of gemcitabine, preventing the drug from enzymatic degradation. Systemic administrations of ATF-IONP-Gem significantly inhibited the growth of orthotopic human pancreatic cancer xenografts in nude mice. With MRI contrast enhancement by IONPs, we detected the presence of IONPs in the residual tumor lesions following the treatment, suggesting the possibility of monitoring drug delivery and assessing drug resistant tumors by MRI. The theranostic ATF-IONP-Gem nanoparticle has great potential for the development of targeted therapeutic and imaging approaches that are capable of overcoming the tumor stromal barrier, thus enhancing the therapeutic effect of nanoparticle drugs on pancreatic cancers.